(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the legislative regulation and law enforcement practice of part-time work in Uzbekistan. This article pays great attention to the legal features of part-time work, in particular the concept of part-time work, the definition of the legal status of part-time workers, the specifics of their hiring, rationing and remuneration, provision of guarantees and compensation, as well as termination of employment relations with this category of employees. The author analyzes various approaches to part-time work in the science of labor law and in practice. In the course of studying part-time work, the author used a number of methods, as well as practical experience from labor relations between employee and employer.